HUMAN DEVELOPMENT AND WELFARE STATE: A CLASSIFICATION ON SELECTED COUNTRIES (Third Sector Social Economic Review, 2023)
Increasing the quality of life of individuals and societies, meeting basic needs, providing access to welfare services, constitute the areas where the concepts of human development and welfare state are common. With the concept of human development expanded by the United Nations Development Programme, it is aimed to increase the quality of life to accompany economic growth and to combat injustice in income distribution. The Programme publishes Human Development Index data every year in accordance with this statement. The welfare state, on the other hand, has historically aimed at similar goals to human development with tools such as social services, social insurance and welfare programs. In the study, a statistical analysis was carried out on the Human Development index and its sub-indexes (life index, education index and gross national product index) data of the United Nations Development Program published in 2021, based on the relationship and commonality between these concepts. The analysis is based on the approach of Esping-Andersen, which is the most used method in the teaching on the definition and classification of the welfare state. Accordingly, five models suitable for the classification of Esping-Andersen and the authors who contributed to it were selected, and a cluster analysis consisting of 33 countries including Turkey along with the countries corresponding to this models was carried out. It is thought that the findings obtained from the study will help to understand the similarities and differences in human development of countries belonging to different welfare state models.
Keywords: Human Development; Human Development Index; Welfare State; Gosta Esping-Andersen; Cluster Analysis